Effect of Pack Carburizing Temperature on the Surface Hardness of ST37 Low Carbon Steel Using Coconut Shell Charcoal: Pengaruh Temperatur Pack Carburizing terhadap Kekerasan Permukaan Baja Karbon Rendah ST37 Menggunakan Arang Tempurung Kelapa - Made Ery Arsana; Hairian Rahmadi; Helanianato (Logic : Jurnal Rancang Bangun dan Teknologi, 2026)
Steel is extensively utilized in engineering and manufacturing industries due to its mechanical reliability, availability, and cost-effectiveness. Low carbon steel ST37, while exhibiting good ductility, weldability, and machinability, possesses relatively low surface hardness and limited wear resistance, restricting its performance in components subjected to friction and mechanical loading. This study aims to evaluate the effect of pack carburizing temperature on the surface hardness of ST37 low carbon steel. The carburizing process was conducted at three different temperatures (900°C, 1000°C, and 1100°C) with a constant holding time of 30 minutes. Coconut shell charcoal combined with CaCO₃ was employed as the carburizing medium, followed by water quenching to promote martensitic transformation. Surface hardness was measured using the Rockwell B (HRB) scale, and statistical analysis was performed to assess data reliability. The experimental results showed a gradual increase in average hardness from 48.3 HRB (untreated) to 48.6 HRB (900°C), 48.9 HRB (1000°C), and 49.1 HRB (1100°C), representing a maximum improvement of 1.65%. Although the increase was relatively modest and statistically non-significant at the 95% confidence level, the consistent upward trend confirms that carburizing temperature influences carbon diffusion behavior and contributes to surface strengthening. These findings indicate that temperature variation plays a role in enhancing the surface characteristics of ST37 steel, while further optimization of soaking time and microstructural analysis is recommended to achieve more substantial hardening performance.